Words matter: finding meaningful job experiences by carefully evaluating job descriptions - Sutton, Kyra Leigh (Henry Stewart Talks, 2021)
Job descriptions, Time allocation, Development opportunities, Qualifications, Skills, Metrics, Work culture, Inclusion